Reflections on the International Convention on the Rights of the Child - Rosas Rosas, Carlos Ernesto Ortiz (2016)
Last September 4 marked the 26 anniversary of Peru’s ratification of the Convention on the Rights of the Child. Since then, the Peruvian State strengthened its commitment to the protection and promotion of children’s rights. In this paper, the implication of two fundamental concepts in the text of the Convention will be covered from a legalpolitical perspective: the legal definition of child and the best interest of the child.